Skills formation and skills matching in online platform work: policies and practices for promoting crowdworkers’ continuous learning (CrowdLearn) - Lehdonvirta, V; Margaryan, A; Davies, H (European Center for the Development of Vocational Training (CEDEFOP), 2019)
A growing number of people are earning some or all of their income from work mediated through digital platforms, in what is variously known as platform-based work, crowdwork, and online gig work, among other names. Emerging research suggests that such crowdwork is an increasingly important new non-standard form of employment around the world, including in Europe (Katz and Krueger, 2016; Huws et al., 2016; Kässi and Lehdonvirta, 2018). The purpose of the CrowdLearn research project is to examine this phenomenon from the perspective of skills development and skills matching, laying the groundwork for potentially new practices and policies in this area. In this report, we build a picture of the current state of the art on this topic within the research literature. The review is structured as follows. We begin with a background section that summarizes some of the broader transformations taking place in economies and labour markets over the past few decades that set the scene for crowdwork. At the end of this section we also present the project’s research questions. This is followed by a brief section that outlines the methodology that we used to identify literature on skills development and skills matching in crowdwork across relevant social science disciplines as well as the human- computer interaction (HCI) subfield of computer science. The literature is then presented as a review structured around the research questions. The overall conclusion from the review is that research on the topic of skills development and matching of online crowdworkers remains as of yet very scarce. However, the existing research gives us hints as to the potentially important dimensions of the phenomenon, and to the big picture of platform-based work, changing skill demands, and public policy.